Microbial communities in the saline lakes of the Vestfold Hills (Eastern Antarctica) - Perriss, SJ; Laybourn-Parry, J (1997)
A detailed survey was undertaken of the microbial communities of 16 saline lakes in the Vestfold Hills (Princess Elizabeth Land, eastern Antarctica), which ranged in salinity from slightly brackish (4-5‰) to hypersaline (maximum: 174‰). Temperatures at comparable sampling depths in the lakes ranged from -12.2°C to +10.5°C. Ranges in the abundances of bacteria, heterotrophic nanoflagellates (HNAN) and phototrophic nanoflagellates (PNAN) were 1.40 x 107 l-1 -1.58 x 1010, 4.83 x 104 l-1 -1.70 x 107 l-1 and 0- 1.02 x 107 l-1, respectively. There was considerable variation across the salinity spectrum, though in the case of bacteria and PNAN significantly higher concentrations of cells were seen in two of the most saline lakes. The autotrophic ciliate Mesodinium rubrum occurred in all but five of the lakes and was found at salinity levels up to 108‰. Heterotrophic ciliates were generally scarce. Dinoflagellates, particularly Gonyau lax c.f. tamarensis, Gyrodinium lachryma and Gym nodinium sp., occurred in the majority of the lakes. On the basis of chlorophyll a concentrations, nutrient levels and microplankton concentrations the lakes spanned the spectrum from ultra-oligotrophic to oligo/mesotrophic. The most saline lakes had much reduced species diversity compared with the less saline environments. Isolation from the marine environment has led to nutrient depletion, simplification and a truncated trophic structure.